Fever and multilobular mass of the right lung in a young adult with asthma - Adamantia Sotiriou; Nikolaos Koulouris; Petros Bakakos (Medical Mycology Case Reports, 2015)
We report a case of a 37-year-old mild asthmatic male presenting with fever, productive cough and chest pain. The chest x-ray showed a multilobular perihilar shadow of the right lung with a mass-like appearance, confirmed by the CT-scan. He was diagnosed with allergic bronchopulmonary aspergillosis (ABPA). ABPA usually manifests as chronic asthma, recurrent pulmonary infiltrates and bronchiectasis. However, it can rarely be seen in patients with mild asthma and with an unusual radiological presentation of a solid mass.